2018
DOI: 10.1002/adsu.201700155
|View full text |Cite
|
Sign up to set email alerts
|

Water‐Processable Amphiphilic Low Band Gap Block Copolymer:Fullerene Blend Nanoparticles as Alternative Sustainable Approach for Organic Solar Cells

Abstract: The preparation of water‐processable nanoparticles (NPs) of polymer semiconductors assembled using an amphiphilic rod‐coil block copolymer (BCP), and their application to active layer sustainable fabrication of organic photovoltaic devices are reported. The hydrophobic rod is a p‐type semiconductor, while the hydrophilic coil is a short chain of poly‐4‐vinylpyridine strongly interacting with [6,6]‐phenyl‐C61‐butyric acid methyl ester (PC61BM). Through miniemulsion technique stable water‐suspended blend NPs are… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
30
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 20 publications
(30 citation statements)
references
References 51 publications
0
30
0
Order By: Relevance
“…To clearly compare them with pure PC60, we additionally made P3HT:PC60 NP as a reference. As shown in SAXS profiles of Figure b, it is found that the aggregated PC60‐ or PC60–PC 61 BM micelles yield a large structure in all NPs, possibly indicating the formation of a shell surrounding the P3HT core particles . Furthermore, the higher scattering intensity showing larger number of particles appears in the P3HT:PC60–CF–PCBM NPs, which can be monitored in the DLS (Figure c).…”
Section: Resultsmentioning
confidence: 80%
See 2 more Smart Citations
“…To clearly compare them with pure PC60, we additionally made P3HT:PC60 NP as a reference. As shown in SAXS profiles of Figure b, it is found that the aggregated PC60‐ or PC60–PC 61 BM micelles yield a large structure in all NPs, possibly indicating the formation of a shell surrounding the P3HT core particles . Furthermore, the higher scattering intensity showing larger number of particles appears in the P3HT:PC60–CF–PCBM NPs, which can be monitored in the DLS (Figure c).…”
Section: Resultsmentioning
confidence: 80%
“…The indistinguishable morphology finally leads to the cluster formation like small particles are gathered within the whole PC60‐PC 61 BM particle (Full synthesis for the particle formation is shown in Figure S9, Supporting Information), its effect can be confirmed in SAXS data (Figure d). In particularly, slightly shifted structure factor peaks at q = 0.0205 Å −1 to the small q value were observed (inset Figure d and Figure S10a, Supporting Information), implying that the size of aggregated PC60 micelles was larger depending on higher PC 61 BM concentration . Through the above data, the estimated PC60–PC 61 BM structures are schematically characterized in Figure e.…”
Section: Resultsmentioning
confidence: 82%
See 1 more Smart Citation
“…As demonstrated by the photographs in Figure 1 , surface plasma treatment of the PDMS substrate is an essential step for ensuring that PS nanoparticles can be deposited from aqueous dispersions onto these high surface energy elastomeric substrates. Surface plasma treatment is a well-known technique that is often applied to improving the wetting properties of aqueous solutions onto hydrophobic layers such as poly(3,4-ethylenedioxythiophene) polystyrene sulfonate or PDMS [ 16 , 35 , 36 ].…”
Section: Resultsmentioning
confidence: 99%
“…However, during their conventional active layers processing, an enormous amount of chlorinated solvent waste is generated, which is dangerous for the human health and the environment [5,9]. To mitigate the negative impact of OSC fabrication on the environment, several strategies have been investigated recently, which include the use of "greener" solvents such as limonene or nonhalogenated benzene derivatives [10][11][12][13], the synthesis of new organic semiconductors that are readily soluble in polar solvents [14], the introduction of water-based organic semiconductor inks [15][16][17], and the development of new coating processes to reduce wastes [18,19]. Although high power conversion efficiencies (PCEs ) well over 10% can be achieved with OSC active layers processed from the abovementioned nonhalogenated solvents, the safety data sheets of these solvents indicate that they remain relatively hazardous to the environment [10,11].…”
Section: Introductionmentioning
confidence: 99%